Modeling longitudinal spin fluctuations in chiral magnets. (6th February 2019) - Belemuk, A M; Stishov, S M
Abstract: We investigate the effect of evolution of energy of longitudinal spin fluctuations on the helimagnetic transition and specific heat in a Heisenberg magnet with the Dzyaloshinskii–Moriya interaction that may arise in a result of applied pressure. Using the classical Monte Carlo calculations for the spin-lattice Hamiltonian accounting for variable spin amplitudes we find that the helical phase transition is pretty robust against the longitudinal spin fluctuations. At the same time the amplitude of the fluctuation hump seen in the specific heat dependence at and its position are significantly affected. Depending on the mode of evolution the hump either shifts to lower or higher temperatures increasing its amplitude with the amplitude of the fluctuations.